Of women and salt [large type] - Garcia, Gabriela, 1984- (Thorndike Press large print basic series., 2021)
"In present-day Miami. Jeanette is battling addiction. Daughter of Carmen, a Cuban immigrant, she is determined to learn more about her family history from her reticent mother and makes the snap decision to take in the daughter of a neighbor detained by ICE. Carmen, still wrestling with the trauma of displacement, must process her difficult relationship with her own mother while trying to raise a wayward Jeanette. Steadfast in her quest for understanding, Jeanette travels to Cuba to see her grandmother and reckon with secrets from the past. A haunting meditation on the tenacity of women who choose to tell their stories despite those who wish to silence them"--Page 4 of cover.